Sporadic Flowering in Bambusa balcooa Roxb. in Supaul District of Bihar, India - Kumar, Sanjib; Jayaraj, R.S.C.; Bordoloi, Satyam; Sharan, Sunil Kumar; Kumari, Shashi; Lakshmi, Jay (Indian Forester, 2021)
Flowering in bamboos is a very rare phenomenon due to their monocarpic nature and long life cycle. In a survey of bamboo clumps of different districts of North-Eastern Bihar, an unusual sporadic flowering in Haraut bamboo (Bambusa balcooa Roxb.) was recorded at three localities in Supaul district. In India William Roxburgh had observed sporadic flowering in B. balcooa for the first time from Purnea district of Northeastern Bihar. After a very long gap of about 150 years sporadic flowering in B. balcooa is being reported from Supaul district of N-E Bihar. Some of the new findings regarding the morphological characteristics of B. balcooa flowering recorded during the present investigation are (1) that only the flowering culms of the specific clump died without setting seeds and other culms continued to grow normally, (2) young shoots were found to emerge naturally both from unflowered and flowered culms and (3) flowering was observed from basal nodes to upper nodes of the flowering culms and even from the cut flowered culms of one clump. The fear of occurrence of natural calamities due to bamboo flowering had no impact on the people of this region.